KAJIAN IKLAN TELEVISI DALAM PERSPEKTIF TEORI PENGARUH SELEKTIF - Susi Evanita (Jurnal Ilmu Komunikasi, 2009)
This study aims to analyzing the influence of television advertisement on the housewives attitude to the product. This analysis used the selective influence theory with selected independent variables, such as the slogan, model, and repetition advertisement, and motivation, age, education, income, jobs, and reference group as well. Attitude to the product as the dependent variable. Research uses analytical survey method with the population are housewives living in Padang. The sample was taken through cluster random sampling technique based on administrative area, there were 390 housewives. The primary data were obtained through questionaire which was designed in accordance with the need of the research, interview, and observation. Documentation was the source of secondary data. Used for path analysis. Research finding show that advertisements of tagline, models, repetitions, motivation, age, education, income, and group reference wholly influence significantly toward to the attitude of this products. Partially only the income doesn’t influence significantly toward attitude to the product.